DIGITAL FRAGMENTATION OF FAITH: POLARIZATION OF ISLAMIC UNDERSTANDING IN DIGITAL SPACES AND ITS SOCIETAL IMPLICATIONS FOR MUSLIM COMMUNITIES - Afried Lazuardi; Agus Nilmada Azmi; Sasikirana Rizky Ramadhania (Karimiyah: Journal of Islamic Literature and Muslim Society, 2025)
The rapid expansion of digital platforms has fundamentally restructured the landscape of Islamic religious discourse, generating conditions in which polarized interpretive communities emerge and consolidate among Muslim populations across the globe. This study investigates the mechanisms through which digital media environments catalyze the fragmentation of Islamic understanding and systematically examines the downstream social consequences for Muslim communities. Employing a systematic literature review methodology with thematic synthesis, we analyzed 48 peer-reviewed studies published between 2018 and 2025, with concentrated attention on scholarship produced between 2021 and 2023. Four principal mechanisms through which digital spaces produce interpretive polarization were identified: (1) algorithmic filtering that generates ideological echo chambers, (2) the unchecked democratization of religious authority enabling unverified interpretive claims to circulate widely, (3) the commodification of Islamic discourse for platform-driven audience engagement, and (4) the progressive erosion of traditional scholarly networks that historically moderated interpretive diversity. These mechanisms produce measurable social consequences, including deepened intracommunal tension, heightened identity-based conflict, the weakening of social cohesion, and the political instrumentalization of religious identity most acutely affecting younger Muslims. Against these tendencies, the study also identifies substantive countervailing forces: cyber-Islamic moderation movements, digital religious literacy initiatives, and organizationally grounded da'wah strategies that demonstrate the viability of constructive digital religious engagement. The theoretical contribution is the concept of "digital religious stratification," which models the structural interplay between platform architecture and Islamic interpretive diversity. These findings carry significant implications for religious educators, policymakers, platform developers, and Muslim civil society organizations committed to cultivating healthier conditions for religious discourse in increasingly digitalized public spheres.